Characterization of Membrane Electrode Assemblies for High‐Temperature PEM Fuel Cells. Issue 5 (12th July 2016) - Rau, M.; Niedergesäß, A.; Cremers, C.; Alfaro, S.; Steenberg, T.; Hjuler, H. A.
Abstract: This paper will present the characterization of two types of membrane‐electrode‐assemblies (MEAs) for high‐temperature polymer electrolyte membrane fuel cells (HT‐PEMFC) working under reformate stream. The important aspects to be considered in the characterization of these MEAs are: (i) presence of contaminants, and (ii) composition of the anode. Start/stop cycling test were performed for two different Dapozol® MEAs using different GDL materials, using first hydrogen and then synthetic reformate as a fuel gas, both with a dew point of 80 °C. With these results the influence of contaminants present in the reformate was compared for the two types of MEAs, showing the superior performance of the Dapozol® 101 MEA under these conditions. The possibility to further enhance the MEAs' resilience against the operation of reformates by changing the anode catalyst composition was evaluated in a half MEA configuration, considering that the impact of the H2 S present in the fuel presents a major issue. For this reason the hydrogen oxidation reaction (HOR) was evaluated for two types of Pt‐based electrocatalysts in an anodic half MEA configuration using different hydrogen‐rich fuel mixtures. These results provide valuable information for the optimization of the MEA and the anode catalyst for HT‐PEMFC.